Toward a typology of food security in developing countries - Yu, Bingxin; You, Liangzhi; Fan, Shenggen (International Food Policy Research Institute, 2010)
The recent global food and financial crises have reversed the last decade's progress in reducing hunger and poverty. This paper conducts a factor and sequential typology analysis to identify groups of countries categorized according to five measures of food security—consumption, production, imports, distribution, and agricultural potential—by using indicators from 175 countries. The analysis first identifies five distinct food security groups, characterized by food intake, and then further splits these groups based on the various measures of food production, trade security, and agricultural potential. The results suggest that the general category of “developing countries” is extremely heterogeneous and is not particularly useful if the focus is on issues of food security. The results also indicate that different responses are needed by different types of food-insecure countries to address the food and financial crises.